Sangre perdida (2020)
Sangre perdida is a creative writing project that proposes a narrative structure based on multiple interconnected stories. Each story narrates a specific event and provides the reader with key information about a character, his or her actions and interactions with other characters. In general, the idea that connects the stories is linked to the existence of a rivalry between two criminal groups interested in accumulating money through betting, sports or casinos. Thus, one of the factions involved in this bid for the betting market is presented as a transnational structure in possession of hotels, casinos, a sports division dedicated to clandestine boxing and, of course, the clandestine betting that derives from these events. This faction is related, has blood ties, with a supernatural entity of universal character. The other faction is made up of Colombians and a pair of foreign, supernatural beings, two voodoo gods of death. This faction is perhaps...